The effect of Electrode Type Differences on BOD and COD Reduction in Tofu Wastewater Treatment - khofifah khofifahparawansyah; Masturah Masturah; Ety Jumiati (Journal of Technomaterial Physics, 2025)
Research has been conducted aimed at testing the results of tofu liquid waste samples on the Biochemical Oxygen Demand (BOD) and Chemical Oxygen Demand (COD) parameters before and after the electrocoagulation process using Al, Cu, and Zn electrodes. This study used tofu liquid waste from Jl. Pasar V Helvetia. The BOD test results before electrocoagulation were 816 mg/L. The BOD test results after electrocoagulation with Al electrodes were 112 mg/L, Cu electrodes were 55 mg/L, and Zn electrodes were 115.2 mg/L. The COD level test results before electrocoagulation were 2696 mg/L. The COD level test results after electrocoagulation with Al electrodes were 95 mg/L, Cu electrodes were 62 mg/L, and Zn electrodes were 105 mg/L. From the electrode variations, the best results were obtained for testing the BOD and COD levels of tofu liquid waste on the Cu electrode.